PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN PERTUMBUHAN ASET PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - Nurochman, Muhammad (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of this study is to determine simultaneous and partial influence of dividend policy, profitability, and growth of corporate assets on the value of companies in the Manufacturing industry listed on the Indonesia Stock Exchange. This research is a quantitative descriptive. Sample consists of 11 companies in manufacturing industry listed on Indonesia Stock Exchange with research period of 5 years starting from 2012 until 2016. The study uses panel data regression with fixed effect model. The result shows that dividend policy, profitability, and growth of company asset simultaneously have significant influence on company value with R square value of 0.9588 means that dividend policy, profitability, and growth of company asset is 95,88% and the rest of 4,12 % influenced by other variables that are not examined. Partially, dividend policy and growth of company asset have non- significant influence on company?s value while profitability has significant influence.